Pemanfaatan Bamboozle untuk Meningkatkan Motivasi Belajar Bahasa Inggris di Kelas XI SMKN 2 Surakarta - Sinta Ari Susanti; Deni Setiawan; Inayatul Jannah; Hefy Sulistyawati; Hindriati Hindriati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
There are various challenges in the learning process that is the low motivation of students especially in learning English. However, motivation has an important role in the learning process. This study aims to enhance motivation in learning English using the interactive learning media Bamboozle among Grade XI students at SMKN 2 Surakarta. This Classroom Action Research (CAR) was conducted in two cycles, involving 36 male students from the Automotive Engineering program. Data collection was performed through observation, interviews, and documentation. The results showed a significant increase in students' motivation across all aspects of the ARCS model (attention, relevance, confidence, and satisfaction) after the implementation of Bamboozle, with average motivation levels rising from 67.5% to 89%. These findings highlight that Bamboozle can enhance students' intrinsic motivation and overall engagement in the learning process. The implications of this study suggest that integrating interactive media like Bamboozle can significantly improve students' motivation and learning outcomes in learning English.